2002
DOI: 10.1620/tjem.196.281
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Changes in Urinary Bicarbonate, Nitric Oxide Metabolites and pH in Female Player during Handball Camp Involved in an Exercise, Rest and Sleep Cycle.

Abstract: Bicarbonate and nitric oxide levels are important humoral factors in the blood and are affected by the human body's physical condition. There are few reports, however, on changes in blood bicarbonate and nitric oxide levels during exercise and rest. Since urinary bicarbonate and nitric oxide metabolites reflect the levels of bicarbonate and nitric oxide in the blood, we studied circadian changes in 6 female athletes by monitoring their urinary pH and their levels of urinary bicarbonate and nitric oxide metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Therefore, this strategy involves training sessions performed at high intensity with in comparison to the ones regularly carried out (15) . However, it has been reported that long periods of high intensity activities during the training camps can cause noticeable physiological disorders in the athletes (16,17) , such as eating behavior disorders, severe muscle damage and dehydration/electrolytes loss (18,19) . Thus, Fry et al (20) state the importance of suitable training loads periodization, with sufficient recovery periods in order to avoid undesired adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this strategy involves training sessions performed at high intensity with in comparison to the ones regularly carried out (15) . However, it has been reported that long periods of high intensity activities during the training camps can cause noticeable physiological disorders in the athletes (16,17) , such as eating behavior disorders, severe muscle damage and dehydration/electrolytes loss (18,19) . Thus, Fry et al (20) state the importance of suitable training loads periodization, with sufficient recovery periods in order to avoid undesired adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recently confirmed the presence of time-of-day effects of exercise on these variables 34, 35. Therefore, health and disease outcomes in response to exercise may depend on the time of day the exercise is performed 36, 37. Hobson et al 38 suggest the existence of a time-of-day effect on aerobic exercise for improving aerobic exercise capacity.…”
Section: Differential Effect Of Exercise Typementioning
confidence: 99%
“…Marked increase of urinary bicarbonate and pH means that the blood pH will become acidified by leftover hydrogen ion in the blood. This blood acidification may correlate with fatigue after heavy exercise (Moriguchi et al 2002b). In spite of these facts, there are few reports on the changes in urinary HCO3 − during and after systemic exercise because urinary HCO3 − has usually been considered negligible, and urinary pH is around 5.5 (Pitts et al 1949).…”
mentioning
confidence: 99%